Freedom and obligatory performance of a contract in the civil law of Ukraine - Yu. M. Zhornokui (Bulletin of Kharkiv National University of Internal Affairs)
An analysis of the legislation of Ukraine, as well as doctrinal approaches and judicial practice regarding the understanding of freedom and obligation to perform a contract in the civil law of Ukraine, has been carried out. It has been concluded that the legislation in many respects creates situation where the principle of freedom of contract is restricted. At the same time, neither legislation nor law-enforcement practice contain any reservations that would allow changing the relevant state of affairs in favor of the principles of dispositive regulation of private law relations.